2009
DOI: 10.1063/1.3097134
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants calculation with a simple mixed quantum/classical implementation of the flux-flux correlation function method

Abstract: A simple mixed quantum/classical (mixed-Q/C) implementation of the flux-flux correlation function method has been applied to evaluate rate constants for a two-dimensional model system. The model consists of an Eckart barrier resembling the collinear H + H(2) reaction, linearly coupled to a harmonic oscillator. Results are presented for a broad range of parameters for temperatures between 140 and 300 K. It is found that the mixed-Q/C method gives fairly accurate results as long as the reaction does not involve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Miller et al23 demonstrated that the rate constants for a gas‐phase reaction can be accurately calculated from where Q r ( T ) is the reactants partition function per unit volume and C ff ( t ) is the flux–flux correlation function, Here F̂ = [ Ĥ , h ] is the flux operator, h is the Heaviside step function, β = ( kT ) −1 , and F̂ (β) is the Boltzmannized flux operator By introducing the spectral decomposition of F̂ (β) into Eq. (2), a numerically convenient expression is obtained to evaluate C ff ( t )20, In this expression, f j and | u j 〉 are the eigenvalues and eigenfunctions of F̂ (β), respectively, N f is the number of such eigenfunctions with non‐negligible eigenvalues, and the | u j ( t )〉 is the time‐evolved eigenfunction of F̂ (β), To perform the mixed‐Q/C computations, the Hamiltonian is written as1, 20 In this equation, Ĥ s is the quantum Hamiltonian of the “system,” which only groups a selected set of coordinates, s , and their conjugated momenta. Ideally, s includes all the modes directly involved in the reactive event.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller et al23 demonstrated that the rate constants for a gas‐phase reaction can be accurately calculated from where Q r ( T ) is the reactants partition function per unit volume and C ff ( t ) is the flux–flux correlation function, Here F̂ = [ Ĥ , h ] is the flux operator, h is the Heaviside step function, β = ( kT ) −1 , and F̂ (β) is the Boltzmannized flux operator By introducing the spectral decomposition of F̂ (β) into Eq. (2), a numerically convenient expression is obtained to evaluate C ff ( t )20, In this expression, f j and | u j 〉 are the eigenvalues and eigenfunctions of F̂ (β), respectively, N f is the number of such eigenfunctions with non‐negligible eigenvalues, and the | u j ( t )〉 is the time‐evolved eigenfunction of F̂ (β), To perform the mixed‐Q/C computations, the Hamiltonian is written as1, 20 In this equation, Ĥ s is the quantum Hamiltonian of the “system,” which only groups a selected set of coordinates, s , and their conjugated momenta. Ideally, s includes all the modes directly involved in the reactive event.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent article1 we applied a mixed‐quantum/classical (Q/C) version of the flux–flux correlation function method to directly calculate thermal rate constants for a model system. The model, previously introduced by McRae et al2 consisted of an Eckart barrier resembling the collinear H + H 2 → H 2 + H reaction, bilinearly coupled to a harmonic oscillator.…”
Section: Introductionmentioning
confidence: 99%